Implementation of the Discovery Learning Model to Improve Students’ Communication Skills in Social Studies Learning at Daarussalaam Junior High School - Sastria Darul Ulfahmi; Nurul Ratnawati; Sonny Soriano (UIN Fatmawati Sukarno Bengkulu, 2024)
The teaching and learning process for Class IX A students at SMP Daarussalam Jakarta tends to be passive. Therefore, it is necessary to implement the discovery learning model to improve students' communication skills. This study aims to describe the implementation of the discovery learning model to enhance communication skills in Class IX A students at SMP Daarussalaam Jakarta. The method used in this research was Classroom Action Research (CAR) using the Kemmis and McTaggart model. The study was conducted over 2 cycles with four stages consisting of planning, implementation, observation, and reflection. Data collection techniques used in this research included observation, interviews, and documentation. Data analysis techniques were used to measure students' communication skills using percentages. The results of this study indicate that learning with the discovery learning model can improve the communication skills of Class IX A students at SMP Daarussalaam Jakarta. This is evidenced by the data obtained. In cycle 1, only 23% of students met the very good communication skills category, while 20% of students were still in the fair category. Compared to cycle 2, it shows that 57% of students have a very good category, then 43% of students have a good category, and there are no longer any students in the fair or poor category. Therefore, learning through the discovery learning model needs to be implemented in the learning process to improve students' communication skills.